MOLECULAR BIOLOGY AND DRUG THERAPIES OF CHRONIC MYELOID LEUKEMIA: A REVIEW OF RECENT LITERATURE - Sameen Shahid; Muhammad Farooq Sabar; Zafar Iqbal; Muhammad Zafar Saleem; Muhammad Abbas Khokhar; Sana Ashiq (International Journal of Pharmacy & Integrated Health Sciences, 2024)
Background: Chronic myeloid leukaemia (CML) is a clonal myeloproliferative disorder of blood stem cells, which is typically characterized by the presence of a Philadelphia chromosome. Even though there have been several studies on the molecular genetics, pharmacogenomics, pharmacological treatments for CML, and its mechanism is still not fully understood. Objectives: This study is designed to provide new updates and better insights into CML molecular biology and drug therapy, along with their benefits and drawbacks. Methodology: For this review, the recent literature was searched from January 2019 to 2023 through various electronic databases. Results: Review findings further suggested that imatinib mesylate was the first tyrosine kinase inhibitor (TKI) licensed as first-line therapy for affected people with CML in the chronic, blast, and rapid phases. Dasatinib is another second-generation multi-target kinase inhibitor, for imatinib-resistant CML treatment in all stages, which is 325 times more effective than imatinib and 16-fold more effective than nilotinib. Nilotinib received approval from the Food and Drug Administration (FDA) for handling imatinib-resistant patients. Bosutinib and ponatinib are other renowned TKIs taken orally. European Medicine Agency (EMA) and FDA-approved asciminib in moderate to severe, rapid, and blast-phase CML patients intolerant to previous therapies. Conclusion: In conclusion, this study indicated the need to include advanced computational tools in addition to the large sample size of cohort studies, which may result in a better understanding of pathophysiology and better clinical outcomes.